Photometric observations of nine Transneptunian objects and Centaurs. Issue 2 (13th November 2017) - Hromakina, T; Perna, D; Belskaya, I; Dotto, E; Rossi, A; Bisi, F
Abstract: We present the results of photometric observations of six Transneptunian objects and three Centaurs, estimations of their rotational periods and corresponding amplitudes. For six of them we present also lower limits of density values. All observations were made using 3.6-m TNG telescope (La Palma, Spain). For four objects – (148975) 2001 XA255, (281371) 2008 FC76, (315898) 2008 QD4, and 2008 CT190 – the estimation of short-term variability was made for the first time. We confirm rotation period values for two objects: (55636) 2002 TX300 and (202421) 2005 UQ513, and improve the precision of previously reported rotational period values for other three – (120178) 2003 OP32, (145452) 2005 RN43, (444030) 2004 NT33 – by using both our and literature data. We also discuss here that small distant bodies, similar to asteroids in the Main belt, tend to have double-peaked rotational periods caused by the elongated shape rather than surface albedo variations.